Intervention effects of high-intensity interval exercise and moderate-intensity continuous exercise on executive functions in obese adolescents with low socioeconomic status - Wang, Xiaotao (Frontiers in Psychology, 2026)
ObjectiveThis study aimed to compare the intervention effects of high-intensity interval exercise (HIIE) and moderate-intensity continuous exercise (MICE) on the executive functions of obese adolescents with low socioeconomic status (SES).MethodsA total of 84 obese adolescents aged 12 ~ 15 years with low SES were selected and randomly divided into three groups: the HIIE group, the MICE group, and the control group, with 28 participants in each group. The HIIE group underwent 12 weeks of combined aerobic and anaerobic training, performed 3 times per week for 60 min each session. The MICE group conducted 12 weeks of outdoor jogging, 3 times per week for 60 min each session. The control group maintained their normal daily life and academic activities. The GO/NOGO task, 2-back task, and More-odd shifting task were used to assess inhibitory control, working memory, and cognitive flexibility, respectively. Meanwhile, body mass index (BMI) and heart rate were monitored throughout the study.ResultsAfter the intervention, both the HIIE group and the MICE group showed significant improvements in inhibitory control, working memory, and cognitive flexibility (all p < 0.05). Specifically, the MICE group exhibited a more significant increase in the accuracy rate of inhibitory control (F = 3.721, p = 0.029, η2 = 0.100), while the HIIE group demonstrated a more pronounced reduction in the reaction time of cognitive flexibility (F = 5.343, p = 0.007, η2 = 0.138). Regarding BMI, the HIIE group had a significantly lower BMI than both the MICE group (p = 0.027) and the control group (p < 0.001), and the MICE group also had a significantly lower BMI than the control group (p = 0.008).ConclusionBoth HIIE and MICE can effectively improve the executive functions and BMI of obese adolescents with low SES, but they exert selective promoting effects. HIIE is more advantageous in improving BMI and reducing the reaction time of cognitive flexibility, while MICE is superior in enhancing the accuracy rate of inhibitory control.